Sensors: A Droplet‐Based High‐Throughput SERS Platform on a Droplet‐Guiding‐Track‐Engraved Superhydrophobic Substrate (Small 7/2017). Issue 7 (February 2017) - Shin, Sera; Lee, Jaehong; Lee, Sanggeun; Kim, Hyunchul; Seo, Jungmok; Kim, Dayeong; Hong, Juree; Lee, Soonil; Lee, Taeyoon
Abstract : A droplet‐based real‐time surface‐enhanced Raman scattering (SERS) sensor is developed based on a superhydrophobic SERS‐active Ag dendritic substrate for high‐throughput real‐time molecular detection, by Taeyoon Lee and co‐workers in article number 1602865. The droplet‐guiding‐track‐engraved superhydrophobic substrate enables individual droplet manipulation and exhibits an enhancement factor of 6.3 × 10 5 . Based on the individual manipulation and SERS measurement of analyte droplets, high‐throughput SERS monitoring can be successfully achieved without spectral interference.